Plan of Attack - Woodward, Bob, 1943- (London Pocket Books, 2004)
The paperback edition of Bob Woodward's critically acclaimed behind-the-scenes look at the Bush administration and it's allies during the controversial war in Iraq.
Include Index and Illustration
Keywords: United States -- Diplomatic relations -- Iraq War (2003-2011)